Biotreatment of oily sludge by a bacterial consortium: Effect of bioprocess conditions on biodegradation efficiency and bacterial community structure - Hentati, Dorra; Abed, Raeid M. M.; Abotalib, Nasser; El Nayal, Ashraf M.; Ashraf, Ijaz; Ismail, Wael (Frontiers in Microbiology, 2022)
We studied the biodegradation of oily sludge generated by a petroleum plant in Bahrain by a bacterial consortium (termed as AK6) under different bioprocess conditions. Biodegradation of petroleum hydrocarbons in oily sludge (C11-C29) increased from 24% after two days to 99% after 9 days of incubation in cultures containing 5% (w/v) of oily sludge at 40 °C. When the nitrogen source was excluded from the batch cultures, hydrocarbon biodegradation dropped to 45% within 7 days. The hydrocarbon biodegradation decreased also by increasing the salinity to 3% and the temperature above 40 °C. AK6 tolerated up to 50% (w/v) oily sludge and degraded 60% of the dichloromethane-extractable oil fraction. Illumina-MiSeq analyses revealed that the AK6 consortium was mainly composed of Gammaproteobacteria (ca. 98% of total sequences), with most sequences belonging to Klebsiella (77.6% of total sequences), Enterobacter (16.7%) and Salmonella (5%). Prominent shifts in the bacterial composition of the consortium were observed when the temperature and initial sludge concentration increased, and the nitrogen source was excluded, favoring sequences belonging to Pseudomonas and Stenotrophomonas. The AK6 consortium is endowed with a strong oily sludge tolerance and biodegradation capability under different bioprocess conditions, where Pseudomonas spp. appear to be crucial for hydrocarbon biodegradation.